Digitalization and its impact on business processes : a case study of skybridge's salesforce implementation - Kanatbekov, Zhanat (2024)
The concept of digital transformation has a significant impact on multiple facets of both the corporate sector and society. Digital transformation refers to the process of incorporating and assimilating digital technologies to generate novel or alter existing corporate procedures, commodities, amenities, and consumer interactions. Customer relationship management (CRM) systems are regarded as a pivotal technology that facilitates the process of digital transformation. These software platforms play a crucial role in assisting organisations in effectively managing and enhancing their engagements with both existing customers and potential prospects. the customer Relationship Management (CRM) solutions offer a multitude of advantages for enterprises, encompassing enhanced levels of client happiness, loyalty, retention, and profitability. This thesis offers an examination of Skybridge, a corporation specialising in cloud-based solutions for the purposes of data integration, analytics, and visualisation. Skybridge adopted Salesforce, a prominent customer relationship management (CRM) technology, to revolutionise and digitise its sales and marketing procedures. The thesis is structured into five distinct segments. Chapter 1 provides an overview of the history and contextual factors relevant to the case study, along with an elucidation of the research's objective and scope. In Chapter 2, an examination is conducted on the existing body of literature pertaining to digital transformation and Industry 4.0, specifically exploring the associated technologies. The primary emphasis is placed on Customer Relationship Management (CRM) systems and the Salesforce platform. In Chapter 3, an examination is conducted on the significance of Customer Relationship Management (CRM) within the context of digital transformation. Additionally, a comprehensive evaluation is presented about the business operations, products/services, and SWOT analysis of Skybridge.